2019
DOI: 10.1002/bjs5.50241
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic proximal gastrectomy with double-flap technique versus laparoscopic subtotal gastrectomy for proximal early gastric cancer

Abstract: Background Laparoscopic proximal gastrectomy with double‐flap technique (LPG‐DFT) and laparoscopic subtotal gastrectomy (LSTG) may replace laparoscopic total gastrectomy (LTG) for proximal early gastric cancer. The aim of this study was to evaluate short‐ and long‐term outcomes after LPG‐DFT and LSTG. Methods Patients who underwent LPG‐DFT or LSTG at the Cancer Institute Hospital in Tokyo between January 2006 and April 2015 were included in this retrospective study. Operative procedures were selected based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…Additionally, it was found that the preventive reflux methods within several techniques increased the incidence of residual food, reflux esophagitis, anastomotic stricture, and anastomotic leakage in all the reconstruction methods, but DFT recorded in the studies observed low incidence of complications 8.9%, 5.5%, 1.4% and 3.9% respectively. Individual studies also recorded a low incidence of complications [22,31,37,40,44]. DFT conducted after proximal gastrectomy seemed to be proven effective to lower the outcome as compared to the procedures of DTR, JPI, JI, and EG.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, it was found that the preventive reflux methods within several techniques increased the incidence of residual food, reflux esophagitis, anastomotic stricture, and anastomotic leakage in all the reconstruction methods, but DFT recorded in the studies observed low incidence of complications 8.9%, 5.5%, 1.4% and 3.9% respectively. Individual studies also recorded a low incidence of complications [22,31,37,40,44]. DFT conducted after proximal gastrectomy seemed to be proven effective to lower the outcome as compared to the procedures of DTR, JPI, JI, and EG.…”
Section: Discussionmentioning
confidence: 98%
“…The remaining 29 studies were included as shown in senmaru et al [26], kameyama et al [21], isobe et al [27], kazuhiro et al [28], adachi et al [29], kondoh et al [30], yasuda et al [32], ahn et al [45], nomura et al [33], sugiyama et al [46], tokunaga et al [35], ohashi et al [47], tanaka et al [38], aburatani et al . [40], nakamura et al [41], katai et al [16], masuzawa et al [42] and takayama et al [43], kano et al [44], koruda et al [22], omori et al [31], and saeki et al [37], 2 papers from Korea, Kim et al [23] and yang et al [34], and 1 paper from Scotland, wright et al [36]. Studies reported postoperative outcomes such as reflux esophagitis, anastomotic leakage, anastomotic stricture, and residual food shown in Table 2.…”
Section: General Characteristic Of the Analyzed Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting decision‐making question is whether to choose PG or subtotal gastrectomy for EGC of the upper stomach 21 . Subtotal gastrectomy may be possible for lesser curvature lesions 3 cm from the EGJ.…”
Section: Indications For Pgmentioning
confidence: 99%
“…PNI) are presented in Table3 [37][38][39]. Kosuga et al39 first reported that patients undergoing LSTG had a significantly higher postoperative BW, and serum Alb and TP levels, than those undergoing LTG.…”
mentioning
confidence: 99%